Optimization of Aspergillus niger rock phosphate solubilization in solid-state fermentation and use of the resulting product as a P fertilizer - Mendes, Gilberto de Oliveira (Microb Biotechnol, 2015)
A biotechnological strategy for the production of an alternative P fertilizer is described in this work. The fertilizer was produced through rock phosphate (RP) solubilization by Aspergillus niger in a solid-state fermentation (SSF) with sugarcane bagasse as substrate. SSF conditions were optimized by the surface response methodology after an initial screening of factors with significant effect on RP solubilization. The optimized levels of the factors were 865 mg of biochar, 250 mg of RP, 270 mg of sucrose and 6.2 ml of water per gram of bagasse. At this optimal setting, 8.6 mg of water-soluble P per gram of bagasse was achieved, representing an increase of 2.4 times over the non-optimized condition. The optimized SSF product was partially incinerated at 350°C (SB-350) and 500°C (SB-500) to reduce its volume and, consequently, increase P concentration. The post-processed formulations of the SSF product were evaluated in a soil–plant experiment. The formulations SB-350 and SB-500 increased the growth and P uptake of common bean plants (Phaseolus vulgaris L.) when compared with the non-treated RP. Furthermore, these two formulations had a yield relative to triple superphosphate of 60% (on a dry mass basis). Besides increasing P concentration, incineration improved the SSF product performance probably by decreasing microbial immobilization of nutrients during the decomposition of the remaining SSF substrate. The process proposed is a promising alternative for the management of P fertilization since it enables the utilization of low-solubility RPs and relies on the use of inexpensive materials.